Respuesta :

Answers:

-32

-8

-2

4

Step-by-step explanation:

[tex]y = 6x - 2[/tex]

[tex]y_1 = 6(-5) - 2 = -30 -2 = -32[/tex]

[tex]y_2 = 6(-1) - 2 = -6 -2 =-8[/tex]

[tex]y_3 = 6(0) - 2 = 0 -2 = -2[/tex]

[tex]y_4 = 6(1) - 2 = 6 -2 = 4[/tex]

Step-by-step explanation:

Ok so the function rule is: y=6x-2

We have 4 sets of numbers under the value "x." That means we have to input the given values into the function.

First is x=-5. We input -5 into the function so we get y=6(-5)-2. We multiply 6 and -5 and we get -30, then we subtract 2 from -30. Then for the answer for the first column, we get -32 for the y value.

Now we have x=-1. We input the number for x in the function and we get y=6(-1)-2. We multiply 6 and -1 and we get -6, then we subtract -2 from -6 and we get -8. So out y value for the second row is -8.

Try the next two on your own to see if you understand. If you still don't understand please comment under this answer. I'll try to respond as quickly as I can.